Dukut Hendronoto: Animator Pertama Indonesia - Rista Ihwanny; Kus Sudarsono; Annita Annita (Institut Seni Indonesia Yogyakarta, 2023)
Along with the massive development of technology, the artworks in the form of animation are increasingly produced. Indonesia is responding to the massive development of the animation industry with producing animation artworks such as advertisements, TV series, and also movies. This burgeoning industry is also supported by the increasing number of educational institutions that offer to teach animation production. This progress is unfortunately not accompanied by the emergence of researches related to the history of animation development in Indonesia. This study aims to introduce Pak Ooq (Dukut Hendronoto), Indonesia’s first animator. Very few have researched the history of Indonesian animation, especially the role of Pak Ooq in the development of Indonesian animation. By interviewing people closest to Pak Ooq, this research tries to explore his life and his works. This research certainly tries to pave the way for more researches to be carried out on the history of Indonesian animation and the important figures who contributed to its development.